Peran Pemerintah Daerah Dalam Pengelolaan Daya Tarik Wisata Alam di Kabupaten TTS: Studi Kasus Daya Tarik Wisata Pantai Oetune - Nugraha, Yudha Eka; Enga, Elisabet Rambu Lika (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2021)
As one of the natural tourist attractions that continues to experience an increase in tourist visits, Oetune Beach requires planned management from various stakeholders, one of which is the local government. The purpose of this research is to describe the government role in the management of Oetune Beach in Tuafanu Village. The research used a qualitative descriptive approach and data were obtained from field observations, interviews, documentation, and literature studies on Oetune Beach from various available sources. Based on the results of the research, it was found that the role of the local government (TTS tourism office) in managing the tourist attraction of Oetune Beach which runs through 4 roles, namely the role of coordinator, developing strategies and policies for managing Oetune Beach in making infrastructures such as access roads to tourist attractions, provision of electricity, and clean water in the oetune beach area. The role of the facilitator is by providing facilities and infrastructure at the Oetune Beach DTW, conducting tourism promotions and guiding each sub-district to identify tourist attractions in each region. The role of the stimulator is carried out through the involvement of local communities as coastal managers. The role of a motivator is carried out through a community empowerment program that provides land to open the tourist attraction of Oetune Beach at no cost to local communities.